2011
DOI: 10.1021/ef2003766
|View full text |Cite
|
Sign up to set email alerts
|

Reforming of Volatiles from the Biomass Pyrolysis over Charcoal in a Sequence of Coke Deposition and Steam Gasification of Coke

Abstract: Nascent volatiles from the pyrolysis of a type of woody biomass were reformed in a bed of charcoal at 750À850 °C. While the volatiles passed through the bed together with air at an air ratio of 0.115, the concentration of heavy tar (bp > 336 °C) decreased from 910 000 to 6À1020 mg/Nm 3 dry . This rapid and almost total decomposition of the tar can be ascribed to its deposition onto the charcoal surface, forming coke. The coke formation leads to the loss of the charcoal micropores that provide active sites. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 30 publications
1
66
0
Order By: Relevance
“…One explanation lies in that char600 had a significantly larger total BET surface area (4.1-fold) and pore volume (2.85-fold) than char800 ( Table 2). It has previously been reported that tar reduction over char surfaces followed two steps of tar deposition to form secondary char and/or coke and steam gasification of coke 4,22 . Although no external steam was introduced, the steam gasification presumably could have taken place from the pyrolytic steam that was generated from the biomass pyrolysis 23,24 .…”
Section: Effect Of Coal Char On Rice Straw Pyrolysismentioning
confidence: 99%
“…One explanation lies in that char600 had a significantly larger total BET surface area (4.1-fold) and pore volume (2.85-fold) than char800 ( Table 2). It has previously been reported that tar reduction over char surfaces followed two steps of tar deposition to form secondary char and/or coke and steam gasification of coke 4,22 . Although no external steam was introduced, the steam gasification presumably could have taken place from the pyrolytic steam that was generated from the biomass pyrolysis 23,24 .…”
Section: Effect Of Coal Char On Rice Straw Pyrolysismentioning
confidence: 99%
“…It results from thermal decomposition of organic compounds onto the catalyst, which results in catalyst deactivation. High and suitable steam to carbon ratio helps decreasing tar and coke formation (Hosokai et al, 2011;Park et al, 2010;Song et al, 2015;Umeki et al, 2012;Wang et al, 2014). However, the heat load increases, since more steam has to be supplied (Moghadam et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the removal of AAEM species, in other words, the major catalytic species, will considerably change the characteristics of gasification of char 26−29 and reforming of volatiles over the char. 30,31 The gasification of char from the pyrolysis of biomass is contributed by non-catalytic gasification and AAEM-catalyzed gasification. 29 These two modes of gasification differ clearly from each other regarding the rate of reaction and its variation with the progress of char conversion.…”
Section: Introductionmentioning
confidence: 99%